5.5.

a11 x1 + a12 x2 +... + a1n xn = b1,

a21 x1 + a22 x2 +... + a2n xn = b2, (5.1)

... ... ... ...

am1 x1 + am1 x2 +... + amn xn = bm.

, . . A ( ) `A , - a) r = n; ) r < n:

) r = n, n n , D . , ;

) r < n, .

x r+1, x r+2,..., xn, , ; :

a11 x1 + a12 x2 +... + a1r xr = b1 - a1,r+1 xr+1 -... - a1nxn,

a21 x1 + a22 x2 +... + a2r xr = b2 - a2,r+1 xr+1 -... - a2nxn,

... ... ... ... ... ... ... ... ... ...

ar1 x1 + ar2 x2 +... + arr xr = br - ar,r+1 xr+1 -... - arnxn.

x1, x2,..., xr, (r- ) . , x1, x2,..., xr. , r < n .

(5.1) , bi = 0, . . :

a 11 x1 + a12 x2 +... + a1n xn = 0,

a21 x1 + a22 x2 +... + a2n xn = 0, (5.5)

... ... ... ... ... ...

am1 x1 + am1 x2 +... + amn xn = 0.

- , , . , , - (5.5) , , x1 = x2 =... = xn = 0. (5.5) r.

r = n, (5.5); r < n , , , .

- X = (x1, x2,..., xn)T ( A), l,

AX = lX.

l ( A), X. A n.

. , A , A .

A AX = lX (A - lE)X = 0, E- n- :

(a11 -l)x1 + a12x2 +... + a1nxn =0,

a21x1 + (a22 -l)x2 +... + a2nxn = 0,

... ... ... ... ... ... ... ... (5.6)

an1x1 + an2x2 +... + (ann-l)xn = 0.

, , , ..

.

n- l, A, A, - , , A.

A (A - lE)X = 0 (5.6) l .

2.16. , .

x1 + x2 - 2x3 - x4 + x5 =1,

3x1 - x2 + x3 + 4x4 + 3x5 =4,

x1 + 5x2 - 9x3 - 8x4 + x5 =0.

. A `A , :

, r(A) = r(`A) = 2. , :

x1 + x2 - 2x3 - x4 + x5 = 1,

- 4x2 + 7x3 + 7x4 = 1.

x1 x2 , :

x1 + x2 = 2x3 + x4 - x5 + 1,

- 4x2 = - 7x3 - 7x4 + 1,

x2 = 7/4 x3 + 7/4 x4 -1/4, x1 = 1/4 x3 -3/4 x4 - x5 + 5/4 - , . x3, x4, x5 , . , x3 = x4 = x5 = 0 x1= 5/4, x2 = - 1/4. C(5/4, - 1/4, 0, 0, 0) .

2.17. .

2x1 - x2 + x3 + x4 = 1,

x1 + 2x2 - x3 + 4x4 = 2,

x1 + 7x2 - 4x3 + 11x4 = a.

. `. ` ~ , :

x1 + 2x2 - x3 + 4x4 = 2,

5x2 - 3x3 + 7x4 = a-2,

0 = a-5.

, a=5. :

x2 = 3/5 + 3/5x3 - 7/5x4, x1 = 4/5 - 1/5x3 - 6/5x4.

2.18. , :

a1 = (1, 1, 4, 2),

a2 = (1, -1, -2, 4),

a3 = (0, 2, 6, -2),

a4 = (-3, -1, 3, 4),

a5 = (-1, 0, - 4, -7).

. , x1, x2, x3, x4, x5,
(. . 1. .
I), :

x1 a1 + x2 a2 + x3 a3 + x4 a4 + x5 a5 = 0.

:

x1 + x2 - 3x4 - x5 = 0,

x1 - x2 + 2x3 - x4 = 0,

4x1 - 2x2 + 6x3 +3x4 - 4x5 = 0,

2x1 + 4x2 - 2x3 + 4x4 - 7x5 = 0.

, . :

.

, 3, , , (r < n). x1, x2, x4 , :

x1 + x2 - 3x4 = x5,

-2x2 + 2x4 = -2x3 - x5,

- 3x4 = - x5.

: x4 = 1/3 x5, x2 = 5/6x5+x3, x1 = 7/6 x5 -x3.

; x3 x5 , . ,

x1 a1 + x2 a2 + x3 a3 + x4 a4 + x5 a5 = 0

, ; , x5 = 6, x3 = 1. x4=2, x2 = 6, x1=6

6a1 + 6a2 + a3 + 2a4 + 6a5 = 0,

.. .

2.19.

.

. A

.

, = (l - 2)2 × (l+2)2. =0 - l1 = 2 l2 = -2. , A. A l (5.6): l = 2

x1 - x2 = 0, x1 - x2 = 0,

x1 - x2 = 0, Þ 3x2 -7x3 - 3x4 = 0,

3x1 - 7x3 - 3x4 = 0, 5x3 + x4 = 0.

4x1 - x2 + 3x3 - x4 = 0,

, l = 2 a (8, 8, -3, 15), a - . l = -2 :

,

x1+3x2 = 0,

x2 = 0,

x3+x4= 0.

l = -2 b (0, 0,-1, 1), b - .